2019
DOI: 10.1111/tpj.14170
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies on the phyllosphere microbiome: Embracing complexity in host–microbe interactions

Abstract: Summary Environmental sequencing shows that plants harbor complex communities of microbes that vary across environments. However, many approaches for mapping plant genetic variation to microbe‐related traits were developed in the relatively simple context of binary host–microbe interactions under controlled conditions. Recent advances in sequencing and statistics make genome‐wide association studies (GWAS) an increasingly promising approach for identifying the plant genetic variation associated with microbes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 140 publications
(162 reference statements)
1
77
0
Order By: Relevance
“…Using this strategy, many studies revealed the microbial association in the phyllosphere of different plants such as mountain shrubs (Ruiz-Pérez et al 2016), seagrass (Fahimipour et al 2017), subarctic grass (Uroz et al 2016), and equatorial forest canopies (Lambais et al 2006). The studies revealed that plant leaves are colonized by a huge and diverse group of microorganisms, including bacteria, fungi, and viruses (Rastogi et al 2013;Morella et al 2018;Sapp et al 2018;Beilsmith et al 2019). High-throughput molecular methods or culture-independent molecular techniques have interpreted the phyllosphere microbial community today (Table 5.5).…”
Section: How To Study Phyllosphere Microbiome?mentioning
confidence: 99%
“…Using this strategy, many studies revealed the microbial association in the phyllosphere of different plants such as mountain shrubs (Ruiz-Pérez et al 2016), seagrass (Fahimipour et al 2017), subarctic grass (Uroz et al 2016), and equatorial forest canopies (Lambais et al 2006). The studies revealed that plant leaves are colonized by a huge and diverse group of microorganisms, including bacteria, fungi, and viruses (Rastogi et al 2013;Morella et al 2018;Sapp et al 2018;Beilsmith et al 2019). High-throughput molecular methods or culture-independent molecular techniques have interpreted the phyllosphere microbial community today (Table 5.5).…”
Section: How To Study Phyllosphere Microbiome?mentioning
confidence: 99%
“…A rapidly growing body of literature has documented the in uence that the microbiome can have on critical plant traits including disease resistance [2][3][4][5], nutrient acquisition and growth [6][7][8][9], abiotic stress tolerance [10,11], and owering phenology [12,13]. Thus, the microbiome can be viewed as an extended phenotype of the plant genome that can enhance the ability of plants to cope with environmental stressors [1,10,[14][15][16]. A fuller understanding of plant microbiomes is critical for improvements in environmental sustainability [17], agriculture [18], and conservation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Beilsmith et al . () discuss how microbiome GWAS can be used to phenotype microbial taxa or microbial functions, and how these studies provide a view of the plant–microbe interactions that occur in natural environments. They also highlight how future studies will use GWAS to identify plant genes or microorganisms for use in breeding or engineering properties such as yield or pathogen resistance.…”
mentioning
confidence: 99%